EFEKTIVITAS KOMPRES JAHE DAN KOMPRES AIR HANGAT TERHADAP INTENSITAS NYERI SENDI PADA LANSIA DI POSYANDU LANSIA (DESA MINOHOREJO KEC. WIDANG KAB. TUBAN) - Qomariah, Siti; Ubaidillah, Moh (Jurnal Keperawatan Duta Medika, 2024)
ABSTRACTJoint pain is a major problem that occurs in the elderly. Joint paint often lead to impaired mobility, independence functions, participation in activities social development, as well as quality of life and is one of the ten mein causes disability in the country is growing. The purpose of this study was to determine the effectiveness of ginger compresses and warm water compresses on the intensity of joint paint in the elderly at Elderly Posyandu (Minohorejo Village, Widang District, Tuban Regency).The research method used is quasy-experimental with a "nonequivalent control group design" research design. The research sample was 30 elderly in Elderly Posyandu, Minohorejo Village, which were selected by simple purposive sampling. The independent variable in this study was ginger compresses and warm water compresses, and the dependent variable of this study was the joint pain intensity. The instruments used are SOP and NRS sheets. The statistical test used in this study is the Paired Sample T-Test. The results showed that before being given abdominal stretching in the moderate pain category and after being given abdominal stretching in the mild pain category. From the statistical test results obtained p value = 0.000 at = 0.05 (p <0.05), indicating that there is an effect of abdominal stretching on reducing the intensity of dysmenorrhea pain in adolescents Dusun Pandan, Minohorejo Village, Kec. Widang Kab. Tuban. It is hoped that the elderly in Elderly Posyandu Minohorejo Village can play an active role in helping reduce the problems of joint pain, especially the other elderly in Minohorejo Village by teaching ginger compresses and warm water compresses.